2019
DOI: 10.3390/genes10090723
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer in the Pediatric Population

Abstract: Thyroid cancer is rare in the pediatric population, but thyroid carcinomas occurring in children carry a unique set of clinical, pathologic, and molecular characteristics. In comparison to adults, children more often present with aggressive, advanced stage disease. This is at least in part due to the underlying biologic and molecular differences between pediatric and adult thyroid cancer. Specifically, papillary thyroid carcinoma (which accounts for approximately 90% of pediatric thyroid cancer) has a high rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(222 citation statements)
references
References 127 publications
(216 reference statements)
6
172
1
10
Order By: Relevance
“…Furthermore, these indeterminate aspirate diagnoses are associated with increased risk of malignancy in children versus adults (28% in children versus 6-30% in adults for atypia or follicular lesion of undetermined significance (AUS/FLUS) and 58% in children versus 10-40% in adults for follicular/Hürthle neoplasm or suspicious for follicular/Hürthle neoplasm (FN/SFN lesions). However, more recent studies indicate lower percentages of indeterminate FNAB groups than previously reported (13-18% for indeterminate diagnoses combined) and a lower risk of malignancy after histologic resection within these groups (11-20% for AUS/FLUS; 25-28% for FN/SFN) [6].…”
Section: Fine-needle Aspiration Biopsy (Fnab)mentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, these indeterminate aspirate diagnoses are associated with increased risk of malignancy in children versus adults (28% in children versus 6-30% in adults for atypia or follicular lesion of undetermined significance (AUS/FLUS) and 58% in children versus 10-40% in adults for follicular/Hürthle neoplasm or suspicious for follicular/Hürthle neoplasm (FN/SFN lesions). However, more recent studies indicate lower percentages of indeterminate FNAB groups than previously reported (13-18% for indeterminate diagnoses combined) and a lower risk of malignancy after histologic resection within these groups (11-20% for AUS/FLUS; 25-28% for FN/SFN) [6].…”
Section: Fine-needle Aspiration Biopsy (Fnab)mentioning
confidence: 59%
“…Relative to the common pediatric malignancies, such as leukemia, central nervous system (CNS) tumors, and lymphoma, thyroid cancer is rare in pediatric populations, affecting approximately 1 in every 1000 to 2000 children in the United States. However, it is the leading cause of pediatric endocrine cancer, accounting for over 6% of all pediatric cancers [6]. The incidence of thyroid cancer is increased in young adults, accounting for 13% of all invasive neoplasms [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…The incorporation of expanded, next‐generation sequencing (NGS) panels has improved the identification of somatic alterations and allowed for increased accuracy in identifying malignancy in thyroid nodules with indeterminate cytology as well as reclassification of DTC into molecular subtypes that more accurately correlated with differentiation, tumor behavior, and response to therapy 3 . The data in pediatrics are quite limited compared with adults with a comparatively high percentage of pediatric thyroid cancer without an identified somatic alteration 4 …”
Section: Introductionmentioning
confidence: 99%
“…Thyroid carcinoma is the most common malignancy in adolescent and young adult women, and incidence is increasing across all age groups [1][2][3]. Thyroid carcinoma in children presents with several distinct clinical features when compared with that in adults.…”
Section: Introductionmentioning
confidence: 99%